ANALISA DESAIN USER INTERFACE APLIKASI PROTOTYPE SMART SYSTEM IP CAMERA SECURITY BERBASIS APLIKASI ANDROID - Muhammad Syarif Hartawan (JEIS: Jurnal Elektro dan Informatika Swadharma, 2021)
The purpose of this research is as prototype of early study of development of IP camera monitoring application which can be accessed through Android Device, in development of a certain application can not be separated from its initial creation that is user interface design of an application, so in usage application user can understand navigation or button that are in the program. Usefulness of user interface design in user satisfaction of this application in accessing information that resides in the application. The object of this research is the design of user interface prototype android application Smart System IP Camera Security with respondents of 40 respondents. This research data is obtained from questionnaire data to android application user which then processed statistically by using range of category and percentage through Likert scale. The research results show all independent variables (indicator) EUCS, consist of Content (Content), Format (report) Accurancy (Timeliness), Ease of Use (Ease of Use), which has a significant relationship with the needs of users of the android application satisfaction. The results of this study indicate that the level of satisfaction with the overall user interface design fall into the category agree and feel satisfied using the android application, with a percentage of 95%.